Chapter 11 Framing Transdisciplinary Research as an Assemblage A Case Study from a Mental Health Setting - Batterham, Mark (Taylor & Francis, 2023)
In this case study of a transdisciplinary collaboration between a mental health nurse and a human geographer, we reflect on a continuing research venture to develop walking therapy as an accepted intervention in the mental health system. We draw on Gilles Delueuze and Félix Guattari's assemblage theory to frame the research practice, or journey, as something which is boundless, fluid, and constantly evolving. Specifically, we (re)visit four points where the research project is forced to change course and which reveals vulnerabilities such as feelings of powerlessness and the absence of a clear route for our knowledge to be recognised. In the present moment, this is an exercise which has helped us as authors to understand our own passage. For the future, we offer other practitioners of qualitative inquiry an approach that helps them to draw strength and find acceptance in complex and unpredictable scenarios.